Circulation Situation Characteristics of Regional Short-time Heavy Rainfall in Eastern Gansu Province in Summer - Xiangwei KONG; Chenrui LI; Xiumei YANG; Yi YANG; Xiaojun YANG (Gaoyuan qixiang)
The short-time heavy rainfall in eastern Gansu Province is prone to disaster， and difficult to forecast and early warning.Using hourly precipitation data from encrypted meteorological stations and NCEP/NCAR reanalysis data in summer of 2010-2021， 50 regional short-time heavy precipitation events in eastern Gansu Province are Screening out.Based on the geopotential height anomaly field at 500 hPa， a combination of K-mean objective cluster analysis and subjective synoptic verification are used to classify the synoptic-scale circulation situation of these events， and construct different conceptual models of synoptic scale system configuration by analysis-by-synthesis.The results are as follows： （1） The synoptic scale circulation situation of 50 regional short-term heavy rainfall events in eastern Gansu Province can be divided into four types： plateau trough eastward moving type， southwest airflow at the edge of subtropical high type， shear between two high pressures type and northwest airflow type.（2） The southwest airflow at the edge of the subtropical high type causes the largest number of regional short-term heavy rainfall， the plateau trough eastward moving type and the shear between two high pressures type have the same frequency， and the northwest airflow type is least.（3） There are significant differences in weather system configuration， uplift conditions， water vapor conditions and unstable conditions of these four types.When the plateau trough eastward moving type， southwest airflow at the edge of subtropical high type， shear between two high pressures type occur， the position of the western Pacific subtropical high gradually advancing from west to north， and the water vapor conditions and unstable conditions are gradually improving， the baroclinic frontogenesis causes a large range of short-term heavy rainfall when the high trough leads the cold air move to southeast.The uplift condition of the plateau trough moving eastward type is the best， and the falling zone of short-time heavy rainfall is southerly.Under the situation of the shear between two high pressures type， the cold air is northward and mainly enters from the lower troposphere， and the falling zone of short-time heavy rainfall is northward too.The convergence of cold and warm air is the most intense， the baroclinic frontogenesis is the strongest， and the range and intensity of short-term heavy rainfall are also larger.The dynamic conditions and water vapor conditions of the northwest airflow type are the worst in the four types， however， the strong dry and cold advection in the middle and upper layers superimposed with the warm and wet airflow or warm temperature ridge in the lower layer formed the best unstable conditions， and short-term heavy rainfall falling zone is dispersed.